A method for modifying carbonaceous materials with manganese carbonate to module the formation of singlet oxygen via activation with Peroxymonosulfate - Camila Mosquera-Olano; Carolina Quimbaya; Santiago López-Pérez; Elkin Castellón-Castrillón; Sandra Navarro; John Rojas; Jorge Acosta; Ricardo A. Torres-Palma; Yenny P. Ávila-Torres (MethodsX)
This approach examines several agriculture wastes (shell coconut, pseudo-steam banana, potato) as precursors of carbonaceous materials to produce 1O2. The materials were modified with manganese carbonate at 800 °C and then, characterized using DLS (Dynamic Laser Scattering), BET (Brunauer-Emmett-Teller) Method, and zeta potential. Subsequently, the materials were activated via-peroxymonosulfate (PMS, HSO5), and a scavenger to evidence the singlet oxygen formation was used. Acetaminophen, sulphamethoxazole, and losartan were employed as the pharmaceutical targets, evaluating the effects of ROS (reactive oxygen species) in the acetaminophen degradation processes. The methodology of computational calculations was developed to obtain HOMO-LUMO for all systems of modified and unmodified materials in the presence of PMS and acetaminophen to understand both the adsorption and the carbocatalysis processes. This method allows an understanding of the presence of manganese carbonate in thermal synthesis, which determines the modulation of reactive oxygen species depending on the pH of the treatment. This method is significant as follows: • Low-cost carbonaceous materials activated with PMS demonstrated significant efficiency in degrading organic molecules, utilizing singlet oxygen as the primary oxidant. • Theoretical computational approaches investigate the interaction between material and molecule. • The role of carbonate ions in influencing singlet oxygen production in materials derived from residual biomass was examined.